1991
DOI: 10.1021/bi00102a002
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of IgE bound to its receptor Fc.epsilon.RI and in solution

Abstract: Previous resonance energy transfer studies suggested that murine immunoglobulin E (IgE) is bent near the junction of its Fc and Fab segments when bound to its high-affinity receptor (Fc epsilon RI) on RBL cells. To examine further the conformations of IgE, both bound to this receptor and in solution, a mutant recombinant IgE (epsilon/C gamma 3*) was prepared that has a cysteine replacing a serine near the C-terminal ends of the heavy chain. The introduced cysteine residues provide a means for specific modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 27 publications
6
63
0
Order By: Relevance
“…A possible explanation arising from studies on the interaction of rat IgE with its receptor on RBL cells is that IgE adopts a bent conformation which then renders the e-chain inaccessible to a second receptor molecule or to antibodies directed against epitopes in IgE that become masked after receptor engagement. The distance between the V-region and the CE4 domain of IgE in solution or complexed to Fc^.Rl, which would be 18 nm if the tiiolecule had an extended conformation, is only 7.1 nm (66). In the absence of high-resolution structural data, we incorporated these predictions into a model structure for the interaction between a bent form of IgE and Fc^RIa.…”
Section: Mapping Of the Complementary Binding Site Between Hnman Ige mentioning
confidence: 99%
“…A possible explanation arising from studies on the interaction of rat IgE with its receptor on RBL cells is that IgE adopts a bent conformation which then renders the e-chain inaccessible to a second receptor molecule or to antibodies directed against epitopes in IgE that become masked after receptor engagement. The distance between the V-region and the CE4 domain of IgE in solution or complexed to Fc^.Rl, which would be 18 nm if the tiiolecule had an extended conformation, is only 7.1 nm (66). In the absence of high-resolution structural data, we incorporated these predictions into a model structure for the interaction between a bent form of IgE and Fc^RIa.…”
Section: Mapping Of the Complementary Binding Site Between Hnman Ige mentioning
confidence: 99%
“…IgM shares the basic IgE domain architecture with three domains in the Fc part (11). Fluorescence data (12) and the subsequently determined crystal structure (11) of IgE Fc revealed that the IgE Fc is sharply bent. Interestingly, the latest IgM model suggests a similar Fc region with the Cμ4 domains protruding out of the plane defined by Cμ2, Cμ3, and the Fab domains (13).…”
mentioning
confidence: 98%
“…At the time of these scattering studies however, the only crystallographic structures available of antibody molecules were of IgG, and so the chains were modeled based on the principles observed in IgG, resulting in the commonly portrayed structure of the pentamer in which all of the C domains lie within the same plane. However, subsequent fluorescence data of the homologous IgE molecule in solution seemed to indicate that the IgE Fc was actually sharply bent (18). These initial observations were then clearly detailed when the crystallographic structure of the IgE Fc was solved (19), showing that the C 2 domains are bent back toward the C 4 domains by Ϸ60°.…”
mentioning
confidence: 98%